Theoretical and experimental study of precipitation and coarsening kinetics of θ′ phase in Al–Cu alloy. (July 2021) - Chen, Zhongwei; Zhao, Yanni; Zhang, Zhe
Abstract: The microstructural evolution and precipitation kinetics of an Al-4.8 wt% Cu alloy were investigated by transmission electron microscope (TEM) and differential scanning calorimetry (DSC) under different heating rates. The DSC results of quenched Al–Cu alloy obtained at different heating rates were used to calculate kinetics parameters of θ′ precipitation. The activation energy for the precipitate growth obtained by the Kissinger method and the analytical model were determined as 53.54 kJ/mol and 85 ± 5 kJ/mol, respectively. For aged Al–Cu alloys, the typical microstructure of θ′ precipitates and the phase relationship with the matrix were obtained. In addition, θ′ phase coarsening kinetics is in coincident with the classical Liftshitz-Slyozov-Wagner (LSW) theory, and the calculated activation energy suggests that coarsening kinetics of θ′ is controlled by diffusion of Cu in the matrix of the investigated Al–Cu alloy. Highlights: The activation energies of θ′ phase was calculated as 53.54 and 80 90 kJ/mol by Kissinger and Analytical model, respectively. The coarsening activation energy of the θ′ precipitate for aged Al–Cu alloys (230, 260, 290, and 320 °C) was 80.2 kJ/mol. The combination of the Analytical model and LSW can effectively investigate the precipitation kinetics of Al–Cu alloys.